Funcionamiento discursivo de la extrema derecha chilena en prensa y TikTok. Revisionismo histórico a 50 años del Golpe de Estado - Rivera López, Diego (2024)
This article analyzes the discursive functioning used by the far right on TikTok, supported by online press media, in the context of the fiftieth anniversary of the 1973 coup in Chile. The significance of the political milestone, combined with the context of Chilean social outbreak that has allowed this political spectrum to enter the mainstream during and after the social outbreak of 2019-2020, necessitates an alternative approach. Thus, the aim of this work is to understand the discursive articulation, as both practice and political rationality, of the Chilean far right as an exercise in historical revisionism. The study considers 114 relevant TikTok videos published between 2019 and 2023, and the support of a corpus of over 950,000 news  from 77 Chilean digital media outlets. Mixed methods are used to quantitatively analyze media coverage and qualitatively examine narrative structures through Sociology of Knowledge Approach to Discourse (SKAD). The contribution of the text is to propose a reading that highlights the political autonomy of this political sector, which is assumed as a resistance that rebels against a regime of truth regarding the events of the Popular Unity era. Finally, this text contributes to an interdisciplinary discussion that considers data mining methods, discourse analysis, and the integration of sociological, psychological, political, and philosophical theories.